A Small-Molecule Cocktails-Based Strategy in Culture of Mesenchymal Stem Cells - Feng, Yuan; Luo, Jing; Cheng, Jintao; Xu, Aimin; Qiu, Dongbo; He, Sixiao; Zheng, Dayong; Jia, Changchang; Zhang, Qi; Lin, Nan (Frontiers in Bioengineering and Biotechnology, 2022)
Mesenchymal stem cells (MSCs) have a variety of unique properties, such as stem cell multipotency and immune regulation, making them attractive for use in cell therapy. Before infusion therapy, MSCs are required to undergo tissue separation, purification, and expansion in vitro for a certain duration. During the process of in vitro expansion of MSCs, the influence of culture time and environment can lead to cell senescence, increased heterogeneity, and function attenuation, which limits their clinical applications. We used a cocktail of three small-molecule compounds, ACY (A-83–01, CHIR99021, and Y-27632), to increase the proliferation activity of MSCs in vitro and reduce cell senescence. ACY inhibited the increase in heterogeneity of MSCs and conserved their differentiation potential. Additionally, ACY maintained the phenotype of MSCs and upregulated the expression of immunomodulatory factors. These results suggest that ACY can effectively improve the quantity and quality of MSCs.